Pengaruh Kualitas Produk, Inovasi Produk Dan Strategi Pemasaran Terhadap Keunggulan Bersaing (Studi Kasus pada UMKM Batik Tulis Argotirto) - Ahmad Rifqi Mubarok; Siti Asiyah; Ratna Tri Hardaningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the effect of product quality, product innovation and marketing strategy on competitive advantage in SME Batik Tulis Argotirto. The data used in this study used primary data by distributing questionnaires to respondents. The population in this study were consumers of Batik Tulis Argotirto with a total sample of 64 consumers. Sampling technique using Non Probability Sampling. Data collection techniques using questionnaires and data analysis tools. Based on the results of the study simultaneously showed that product quality, product innovation and marketing strategy had a significant effect on competitive advantage in SME Batik Tulis Argotirto. While partially there is an influence between the variables of product quality, product innovation, and marketing strategy on competitive advantage in SME Batik Tulis Argotirto. Keywords: Product Quality, Product Innovation, Marketing Strategy, Competitive Advantage